Self-Inhibiting Modules Can Self-Organize as a Brain of a Robot: A Conjecture - J. Negrete-Martínez (Applied Bionics and Biomechanics)
In this article we describe a new robot control architecture on the basis of self-organization of self-inhibiting modules. The architecture can generate a complex behaviour repertoire. The repertoire can be performance-enhanced or increased by modular poly-functionality and/or by addition of new modules. This architecture is illustrated in a robot consisting of a car carrying an arm with a grasping tool. In the robot, each module drives either a joint motor or a pair of wheel motors. Every module estimates the distance from a sensor placed in the tool to a beacon. If the distance is smaller than a previously measured distance, the module drives its motor in the same direction of its prior movement. If the distance is larger, the next movement will be in the opposite direction; but, if the movement produces no significant change in distance, the module self-inhibits. A self-organization emerges: any module can be the next to take control of the motor activity of the robot once one module self-inhibits. A single module is active at a given time. The modules are implemented as computer procedures and their turn for participation scheduled by an endless program. The overall behaviour of the robot corresponds to a reaching attention behaviour. It is easily switched to a running-away attention behaviour by changing the sign of the same parameter in each module. The addition of a “sensor-gain attenuation reflex” module and of a “light-orientation reflex” module provides an increase of the behavioural attention repertoire and performance enhancement. Since scheduling a module does not necessarily produce its sustained intervention, the architecture of the “brain” is actually providing action induction rather than action selection.